Real-time performance study of a PV solar panel with and without water cooling - Chan, Kevin Min Zin (Nanyang Technological University, 2020)
Photovoltaic (PV) panels experience a varying power output at different panel temperatures. To ensure the panel is operating at its optimal state and without any detrimental long term effects to it, a cooling system is recommended by several studies. This paper studies the efficiency of a PV panel with and without water cooling under tropical environmental conditions and aims to improve its efficiency using different cooling methods. A water cooling system using ambient temperature and solar irradiance as a control was set up on a PV panel. Threshold temperature and solar irradiance of 35℃ and 800W/m2 and cooling water flow rate of 16.7cm3 were used in the cooling system. It was found that power generated for a panel with the temperaturecontrolled cooling system experienced a 5% increase in power output while the panel with the solar irradiance-controlled cooling system experienced a 12% increase in power output compared to a non-cooled panel. The solar irradiance-controlled cooling system also used 55% less water compared to the temperature-controlled cooling system.